Amphoteric composite of ZrP and N-doped porous carbon: Synthesis, characterization, and potential use for cycloaddition of CO2 - Yumiao Zhou; Dong Liang; Yuehua Yao; Lin Chen; Hongjiao Zhang; Yue Wu; Ting Zhao; Na Zhu (Heliyon, 2023)
Composites of amorphous ZrP and N-doped carbon were prepared in a one-step pyrolysis process instead of general post-loading technique. Owing to their mesoporous structure (6–10 nm) and Zr content (up to 41 wt%), the amphoteric materials have potential use in the cycloaddition of CO2 to epoxides, which is an acid‒base tandem process including the ring opening of epoxides and the addition of CO2. Substantial work has been done on how starting materials impact the structure and performance of composite materials. The coordination between metal and melamine has been confirmed, and it can be implanted in the melamine-polymer initiation of formation of porous metal-carbon materials. The composite catalysts exhibit amphoteric properties, present broad-spectrum adsorption, and finally produce carbonates via cycloaddition of CO2 to epoxides. It is remarkable that the multiple characteristics of porous solids are stabilized, and no significant loss of catalytic performance is observed after four cycles.